Interaction Effects of Temperature, Light, Nutrients, and pH on Growth and Competition of Chlorella vulgaris and Anabaena sp. Strain PCC - Meng, Shun Long; Chen, Xi; Wang, Jing; Fan, Li Min; Qiu, Li Ping; Zheng, Yao; Chen, Jia Zhang; Xu, Pao (Frontiers in Environmental Science, 2021)
Interaction effects of temperature, light, nutrients and pH on growth and competition of Chlorella vulgaris and Anabaena sp. strain PCC was carried out by orthogonal design method to research how the environment factors to promote the growth of useful algae and restrain the growth of harmful algae. The results showed that the optimum conditions for growth of Chlorella vulgaris in uni-cultured system were temperature 35 ºC, light 660 lx, N concentration 0.36 mg•L-1, P concentration 0.1 mg•L-1 and pH 9.0 respectively; and that for Anabaena were temperature 30 ºC, light 6600 lx, N concentration 0.18 mg•L-1, P concentration 0.1 mg•L-1 and pH 7.0 respectively. The optimal conditions for the growth of Chlorella vulgaris in co-culture system were temperature 25 ºC, light 4 400 lx, N concentration 0.18 mg•L-1, P concentration 0.5 mg•L-1 and pH 6.0 respectively, while that for Anabaena were temperature 35 ºC, light 4400 lx, N concentration 0.36 mg•L-1, P concentration 0.5 mg•L-1 and pH 6.0 respectively. Both the competition-inhibition parameters of Anabaena against Chlorella vulgaris and that of Chlorella vulgaris against Anabaena were the largest under the conditions of temperature 30 ºC, light intensity 6600 lx, N concentration 0.36 mg•L-1, P concentration 0.025 mg•L-1 and pH 8.0. According to Lotka-Volterra competition model, Anabaena won in the competition in co-culture system with the conditions of (temperature 15 ºC, light 660 lx, TN 0.18 mg•L-1, TP 0.025 mg•L-1, pH 6), (temperature 15 ºC, light 2200 lx, TN 0.36 mg•L-1, TP 0.025 mg•L-1, pH 7), (temperature 15 ºC, light 6600 lx, TN 3.6 mg•L-1, TP 0. 5 mg•L-1, pH 9), (temperature 30 ºC, light 4400 lx, TN 0.18 mg•L-1, TP 0.05 mg•L-1, pH 9), (temperature 35 ºC, light 660 lx, TN 3.6 mg•L-1, TP 0.05 mg•L-1, pH 8), (temperature 35 ºC, light 2200 lx, TN 0.72 mg•L-1, TP 0.025 mg•L-1, pH 9), respectively. However, Chlorella vulgaris couldn`t win in the competition in co-culture system under all the conditions setting in the test.